Integrated production of methanol and biochar from bagasse and plastic waste: A three-in-one solution for carbon sequestration, bioenergy production, and waste valorization - Su G.; Jiang P.; Zhou H.; Zulkifli N.W.M.; Ong H.C.; Ibrahim S. (Elsevier Ltd, 2025)
The shift from fossil fuels to renewable energy is a crucial strategy to achieve carbon neutrality. However, the methanol industry relies heavily on fossil fuels. Alternative feedstocks, such as biomass and plastics, still face many challenges. Biomass is hydrogen-deficient and cannot achieve a high methanol yield, while plastic gasification consumes too much energy. Accordingly, this research proposed a new method to synergistically co-produce methanol and biochar from bagasse pyrolysis and plastic waste gasification. This innovative approach was assessed using techno-economic analysis and hybrid life-cycle assessment based on sugarcane bagasse resources in Guangxi province as a case study and compared with the other four scenarios. The results indicated that the novel method exhibits huger economic and environmental benefits with a low payback period of 6.32 years and a low global warming potential of ?1875.41 kg CO2-eq/t. However, the high total capital cost is the primary potential obstacle to widespread promotion. Spatial-temporal analysis shows that Chongzuo and Laibin have the most tremendous methanol production potential and economic and environmental benefits due to their high bagasse production. This study contributes to biomass utilization and plastic waste management by proposing a synergistic process and offers multiple benefits for carbon sequestration, energy security, and waste valorization. ? 2024 Elsevier Ltd